American autopsy : one medical examiner's decades-long fight for racial justice in a broken legal system / Michael M. Baden, MD. - Baden, Michael M. (BenBella Books, Inc., 2023)
"Dr. Baden chronicles his six decades on the front lines of the fight for accountability within the legal system-including the long history of medical examiners of using a controversial syndrome called excited delirium (a term that shows up in the pathology report for George Floyd) to explain away the deaths of BIPOC restrained by police"-- Provided by publisher.